Effects of plaza dancing on body composition and cardiopulmonary function in middle-aged and the aged healthy women: a systematic review and meta-analysis - Yao, Jiayi; Wang, Haozhe; Jia, Shiguan; Liao, Mingyu; Chen, Wenjia (Frontiers in Public Health, 2025)
Background/objectivesMiddle-aged and older women aged 45 and above face problems of body composition imbalance and declining cardiopulmonary function due to physiological changes during menopause, while traditional exercise interventions have adaptability deficiencies. Plaza dancing, as a form of collective aerobic dance exercise performed to music in open spaces such as plazas and parks, is characterized by low intensity and ease of learning, and has demonstrated health promotion potential. However, there is a lack of systematic evaluation of its comprehensive effects on body composition and cardiovascular function in middle-aged and older women. This study aims to clarify the effectiveness of plaza dancing on body composition and cardiovascular function in healthy middle-aged and older women through systematic review and meta-analysis, and to explore the dose–response relationship of intervention duration.MethodsFollowing the PRISMA guidelines and Cochrane Collaboration Handbook, we systematically searched PubMed, Web of Science, CNKI, Wanfang, and VIP databases (up to July 5, 2025), and included 38 studies meeting the criteria, with 17 studies entering meta-analysis. The Cochrane Risk of Bias tool (ROB 2.0) was used to assess study quality. Statistical analyses were performed using Review Manager 5.4 and R 4.5.1 to calculate standardized mean differences (SMD) or mean differences (MD). Random-effects models (I2 > 50%) or fixed-effects models (I2 < 50%) were applied based on heterogeneity, with subgroup analyses and publication bias assessments conducted.ResultsMeta-analysis revealed that plaza dancing significantly reduced body weight (SMD = −0.27, 95%CI [−0.46, −0.09], p = 0.004), BMI (SMD = −0.59, 95%CI [−0.85, −0.33], p < 0.00001), body fat percentage (SMD = −0.51, 95%CI [−0.82, −0.20], p = 0.001), resting heart rate (SMD = −0.38, 95%CI [−0.68, −0.07], p = 0.02), systolic blood pressure (SMD = −0.42, 95%CI [−0.76, −0.09], p = 0.01), cholesterol (MD = −0.25, 95%CI [−0.48, −0.02], p = 0.03), and triglycerides (MD = −0.20, 95%CI [−0.34, −0.06], p = 0.005), while significantly improving vital capacity (SMD = 0.76, 95%CI [0.25, 1.26], p < 0.0001). Subgroup analysis indicated that BMI improvement was more significant when intervention duration ≤12 weeks (SMD = −0.69). Publication bias assessment showed that results for most indicators were robust. Meta-regression analysis revealed significant dose–response relationships: both BMI (β = 0.043, 95%CI [0.025, 0.061], p < 0.001, R2 = 0.998) and resting heart rate (β = 0.041, 95%CI [0.010, 0.072], p = 0.011) demonstrated significant negative time effects, with greater effect sizes observed in short-term interventions (8–12 weeks). Triglycerides exhibit a unique “bimodal” effect pattern, with both short-term and long-term interventions showing favorable outcomes, while the medium-term effect is relatively attenuated. Assessment of publication bias indicates that the results of most indicators are robust.ConclusionPlaza dancing exerts significant positive effects on body composition and cardiopulmonary function in middle-aged and the aged healthy women, serving as a low-cost, highly accessible health promotion intervention. Future research should conduct large-sample, long-term follow-up studies to optimize intervention protocols and explore underlying mechanisms.Systematic review registrationwww.crd.york.ac.uk/prospero, identifier CRD420251075375.